Saddam's world: political discourse in Iraq - "Bengio, Ofra" (New York, 2002)
This is the first serious attempt to understand modern Iraq through a close examination of the political discourse used by the Ba'th regime and its leader, Saddam Hussein. By analyzing political terms, concepts, and idioms as disseminated through the official Iraqi mouthpieces, author Ofra Bengio illuminates Iraq's political culture and the events that these expressions have both reflected and shaped. Not only does this study add to our understanding of the "Saddam enigma;" it also offers a more universal truth: that under any regime, political culture is built on public discourse. Saddam's Word will be of much interest to students of the contemporary Middle East, as well as to all other observers of Saddam Hussein and his regime.
Keywords: Iraq-Politics and government